2017
DOI: 10.1007/s40262-017-0537-1
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam Clinical Pharmacokinetic Monitoring in Pediatric Patients with Epilepsy

Abstract: Levetiracetam is a broad-spectrum antiepileptic drug (AED) with a unique mechanism of action. Older AEDs can cause serious short- and long-term adverse drug reactions and complications, rendering them undesirable to use in pediatric patients. Characteristics that make levetiracetam a near-ideal AED include its broad spectrum of activity, good tolerability profile, and minimal drug-drug interactions. Clinical pharmacokinetic monitoring (CPM) is often recommended in pediatric patients for certain AEDs due to lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…More recently, there have been reports of the use of levetiracetam as a prophylaxis against busulfan-induced seizures in pediatrics; however, there is little information regarding its use in adults [ 5 , 10 , 11 ]. The pharmacokinetic features of levetiracetam, including approximately 100% bioavailability and linear pharmacokinetics, enable its usage without therapeutic drug monitoring (TDM) [ 12 , 13 ]. Additionally, the drug has no effect on cytochrome P450 metabolic enzymes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there have been reports of the use of levetiracetam as a prophylaxis against busulfan-induced seizures in pediatrics; however, there is little information regarding its use in adults [ 5 , 10 , 11 ]. The pharmacokinetic features of levetiracetam, including approximately 100% bioavailability and linear pharmacokinetics, enable its usage without therapeutic drug monitoring (TDM) [ 12 , 13 ]. Additionally, the drug has no effect on cytochrome P450 metabolic enzymes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to similar safety and efficacy to phenytoin, levetiracetam has a simple twice-daily dosing regimen that does not require loading doses or therapeutic drug monitoring and has no significant drug-drug interactions which can lead to increased busulfan clearance or affect other potential medications patients may require. 10,11,[13][14][15][16]…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our study demonstrates levetiracetam is safe and effective for seizure prophylaxis in pediatric patients and we would propose that levetiracetam be considered as the seizure prophylaxis agent of choice for pediatric patients undergoing HSCT with conditioning regimens which contain busulfan. In addition to similar safety and efficacy to phenytoin, levetiracetam has a simple twice‐daily dosing regimen that does not require loading doses or therapeutic drug monitoring and has no significant drug‐drug interactions which can lead to increased busulfan clearance or affect other potential medications patients may require 10,11,13‐16 …”
Section: Discussionmentioning
confidence: 99%
“…In most pediatric patients with epilepsy treated with levetiracetam, there is no strong indication for a concentration-response association with efficacy or toxicity. It has been suggested that concentrations of levetiracetam do not correlate with the therapeutic value, implying that clinical judgment, without assessing drug concentrations, should be the main strategy [203]. The C3435 T polymorphism of the MDR1 gene has been proposed as a marker to predict drug-resistance in epilepsy [204].…”
Section: Variability In Biological Systems and Response To Asdmentioning
confidence: 99%